Design and Synthesis of Aviram–Ratner‐Type Dyads and Rectification Studies in Langmuir–Blodgett (LB) Films. Issue 30 (1st July 2016) - Jayamurugan, Govindasamy; Gowri, Vijayendran; Hernández, David; Martin, Santiago; González‐Orive, Alejandro; Dengiz, Cagatay; Dumele, Oliver; Pérez‐Murano, Francesc; Gisselbrecht, Jean‐Paul; Boudon, Corinne; Schweizer, W. Bernd; Breiten, Benjamin; et al.
Abstract: The design and synthesis of Aviram–Ratner‐type molecular rectifiers, featuring an anilino‐substituted extended tetracyanoquinodimethane (exTCNQ) acceptor, covalently linked by the σ‐spacer bicyclo[2.2.2]octane (BCO) to a tetrathiafulvalene (TTF) donor moiety, are described. The rigid BCO spacer keeps the TTF donor and exTCNQ acceptor moieties apart, as demonstrated by X‐ray analysis. The photophysical properties of the TTF‐BCO‐exTCNQ dyads were investigated by UV/Vis and EPR spectroscopy, electrochemical studies, and theoretical calculations. Langmuir–Blodgett films were prepared and used in the fabrication and electrical studies of junction devices. One dyad showed the asymmetric current–voltage ( I–V ) curve characteristic for rectification, unlike control compounds containing the TTF unit but not the exTCNQ moiety or comprising the exTCNQ acceptor moiety but lacking the donor TTF part, which both gave symmetric I–V curves. The direction of the observed rectification indicated that the preferred electron current flows from the exTCNQ acceptor to the TTF donor. Abstract : Aviram–Ratner mechanism of rectification : A molecular dyad, closely resembling the original design by Aviram and Ratner, featuring a strong donor (TTF), separated by a rigid insulating σ‐spacer from a strong extended TCNQ acceptor (exTCNQ), has been designed, synthesized, and fully characterized. Langmuir–Blodgett films were prepared and showed the asymmetric current–voltage ( I–V ) curve characteristic for rectification, whereas control compounds containing the TTF but not the exTCNQ unit or featuring the exTCNQ acceptor moiety but lacking the TTF donor showed symmetric I–V curves.